Graphite oxide as an intumescent flame retardant for polystyrene - Kędzierski, M.; Jankowski, P.; Jaworska, G.; Niska, A. (Polimery, 2012)
In this work the possibility to apply graphite oxide (GO) as an intumescent flame retardant added in situ during suspension polymerization of styrene was studied. Synthesis of GO was carried out starting from natural flake graphites with different carbon content and particle size (between 45 and 500 žm). The obtained products were examined using elemental and scanning electron microscopy (SEM) analysis, Fourier transform infrared spectroscopy (FT-IR) as well as X-ray powder diffractometry (XRD). Thermal stability and expansion properties of GO were also investigated. It was stated that with an increase in particle size GO exhibited a lower degree of oxidation while the temperature of maximum decomposition rate increased. The highest expansion volume at 600 °C was observed for GO prepared from graphite with large-sized plates (300 and 500 žm). In order to prevent the dispersion of hydrophilic GO in an aqueous phase during the polymerization of styrene, GO was modified with organofunctional silane. Polystyrene with added GO (15 wt. %) reached HF-1 rating in the UL 94 horizontal burning test, however it failed to pass the required vertical flame test. The modification with melamine-formaldehyde resin (MF) resulted in an increase of GO thermal stability. Polystyrene with 15 wt. % of GO-MF additive obtained maximum ratings HF-1 and V-O in the UL 94 flame test. An attention should be paid to safe handling of GO which, although stable at ambient conditions, may undergo highly exothermic decomposition, e.g. when subjected to mechanical impact at moderately elevated temperature.